Sosialisasi Pemasaran Digital: Profil Google Bisnis, Whatsapp Bisnis, Instagram, dan Facebook Bagi UMKM Desa Rumpia Kabupaten Wajo - Agus Purwanto; Andi Bau Salman; Asrul Jaya; Fuji Pratiwi; Ummi Nurul Herati; Saida Mawarni (YP-SDI Lamaddukelleng, 2025)
MSMEs are a crucial pillar of the village economy, including in Rumpia Village, Majauleng District, Wajo Regency. However, limited digital technology utilization leads to suboptimal product promotion and marketing. This community service activity aims to provide outreach and mentoring for MSMEs in the use of digital platforms such as Google Business, WhatsApp Business, Instagram, and Facebook. The implementation method was door-to-door to be more effective in directly reaching business owners and providing guidance tailored to the needs of each MSME. Pre- and post-tests were conducted (before and after the outreach) to determine the extent of understanding of the use of digital tools in their businesses. The results of the activity showed an increase in MSMEs' understanding and skills in using digital platforms as a marketing tool. This success marks the first step in the digitalization of MSMEs in the village.